Assessment of various WTG (wind turbine generators) production in different Algerian's climatic zones. (1st February 2016) - Saheb Koussa, D.; Koussa, M.; Hadji, S.
Abstract: The present paper estimates the capacity factor of four commercially available WTGs based on the wind characteristics of thirteen sites situated in different Algerian climatic zones. The developed method is validated by comparing the simulated performance values with those estimated from an online Weibull calculator followed by the economical evaluations of electricity generation for three lifetime periods and three interest rate values. From the economic study, it is found that the capacity factors vary from 17% for Bejaïa region to 66% for the Adrar one. In addition, it was found that the minimum cost per kWh of electricity generated is about 0.10 /kWh for Tamenrasset area, which represents the extreme southern region, 0.03 /kWh for Adrar and In salah ones, the south-western region, 0.06 /kWh for Ghardaia, the mid-southern region, 0.07 /kWh for Djelfa, the highland region and finally 0.03 /kWh for Bouzareah, the coastal region. Among all the considered models, the AVANTA AV7 WTG is found to be the most attractive in terms of energy production and cost per kWh. The derived results suggest that the best combination of a WTG and a site corresponds to the choice of the WTG whose cut-in and rated speeds match exactly the wind characteristics of the site. Highlights: Assessment of four wind turbine generators. The study is based on the wind characteristics of various sites situated in Algeria. The capacity factor is estimated. The developed method is validated. Economical evaluations for three lifetime periods and three interest rate values.